(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Mrs. Vinny Therissa Mangam, Assistant Professor, Department of Pharmaceutical Analysis, Aditya College of Pharmacy, Aditya University, Surampalem, Andhra Pradesh, India Abstract Major drug classes involving cardiovascular, respiratory, gastrointestinal, and endocrine conditions represent cornerstone therapies for prevalent chronic diseases. Cardiovascular medications comprises of antihypertensives acting through distinct mechanisms (ACE inhibitors, ARBs, calcium channel blockers, diuretics, beta-blockers), antiarrhythmics classified by electrophysiologic effects, lipid-lowering agents including statins and newer targeted therapies, anticoagulants spanning vitamin K antagonists and direct oral agents, and heart failure medications including beta-blockers, sacubitril/valsartan, and SGLT2 inhibitors demonstrating mortality benefits. Respiratory drugs target bronchospasm through beta-agonists with varying onset and duration profiles; reduce inflammation through inhaled corticosteroids and biological agents targeting specific inflammatory pathways; address allergic responses with antihistamines, leukotriene modifiers, and mast cell stabilizers; and treat pulmonary infections with diverse antimicrobial classes, each requiring specific administration techniques and monitoring parameters. Gastrointestinal agents include acid-suppressing medications (proton pump inhibitors, H2-antagonists), antiemetics targeting central and peripheral pathways, laxatives with mechanical and stimulant mechanisms, antidiarrheals, pancreatic enzymes, and newer biologics for inflammatory bowel disease targeting specific immune pathways. Endocrine medications consist of diabetes therapies including insulins with distinct pharmacokinetic profiles, oral agents with varied mechanisms, and newer injectable therapies; thyroid replacements requiring narrow therapeutic monitoring; reproductive hormones used in contraception and hormone replacement; and osteoporosis treatments spanning bisphosphonates, RANK ligand inhibitors, and anabolic agents, each with specific administration requirements and monitoring needs Keywords: Chronic Disease; Mechanism of Action; Therapeutic Selection; Drug Administration; Monitoring Parameters VIEW PDF